ANALISIS IMPLEMENTASI PENDEKATAN SAINTIFIK DALAM KURIKULUM 2013 KELAS II SDN 079 PEKANBARU - Samosir, Pestaria; Noviana, Eddy; Lazim N, Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to describe the application of the scientific approach in the 2013 curriculum in class II SDN 79 Pekanbaru. This research is a descriptive qualitative research. The subjects in this study were class teachers and all students of class II SDN 79 Pekanbaru. Data collection techniques used in this study include: observation, interviews and documentation. The results showed that teachers and students had carried out learning activities by applying a scientific approach. Activities carried out in learning include observing activities that have been well implemented in learning 1 to learning 6, namely providing opportunities for students to observe images and reading texts. The questioning was not done well from learning 1 to learning 6, only the teacher asked students. Trying activities appear in learning 1 to learning 6 well done such as group discussions, doing independent assignments and coloring. Reasoning activities have been carried out well from learning 1 to learning 6, namely the teacher and students together discussing and solving questions until they reach a conclusion. Communicating activities have been carried out well on learning until learning 6 in the form of communicating in writing or verbally. The teacher gives an explanation of the material, students respond to the teacher's question then students write important information in a notebook. So it can be concluded that teachers and students of class II SDN 79 Pekanbaru have implemented learning by applying a scientific approach but have not been implemented optimally.Key Words: Scientific Approach, 2013 Curriculum